Micropapillary Thyroid Carcinoma: Not So Harmless as it Seems. A 5-Year Follow-Up Cohort Retrospective Study - Fernandes, Urânia; Guidi, Gonçalo; Martins, Daniela; Vieira, Bruno; Leal, Clara; Marques, Rita; Santos, Carlos; Gaspar, João; Pinto-de-Sousa, João (British Journal of Healthcare and Medical Research, 2023)
Introduction: Differentiated thyroid cancer is becoming increasingly prevalent mostly due to the increasing incidence of micropapillary carcinoma. For low-risk tumors, hemithyroidectomy does not reduce survival and may be associated with higher local recurrence. This study aimed to compare Micropapillary versus Papillary thyroid carcinomas regarding overall survival and disease-free survival. Methods: A retrospective, unicentric, cohort study was carried between 2012 and 2016. Consecutive cases with (micro)papillary thyroid carcinoma were enrolled and divided in microcarcinoma group and control group. Exclusion criteria were loss to follow-up, previous thyroid surgery and non-operative treatment. A comparison of several clinical and pathological parameters, recurrence rate and cumulative survival was performed between groups. Results: Patients with micropapillary carcinomas were younger and frequently asymptomatic. 6.5% of these carcinomas presented a benign cytology (Bethesda II) in this study. 18.9% of these patients were submitted to hemithyroidectomy but 71.4% were thereafter totalized. Micropapillary carcinomas presented higher rate of multifocality but similar lymph node invasion rate, lymph node dissection rate and adjuvant iodine therapy. Patients with micropapillary carcinomas presented less advanced staging but similar recurrence rate and time to recurrence; moreover, higher stage was only related with (older) age of presentation. Conclusions: In this study micropapillary carcinomas presented better staging but similar recurrence rate comparing with papillary carcinomas. Moreover, most of these patients were submitted to totalization. These results question if hemithyroidectomy is still a good option for micropapillary carcinomas and if this staging system is adequate. Larger studies with longer follow-up are needed to confirm or refute these results.